Reestruturação produtiva e intermediação de mão-de-obra: a atividade de trabalhadoras de consultorias organizacionais em João Pessoa-PB - Siebra, Sheyla Suzanday Barreto (2009)
This study addressed the activity of professionals engaged in consulting organization, whose number is increasing according to the revocation or dry areas of Human Resources (HR) in business, one of the unfolding of productive restructuring. The recent character of this process led us to explore, from a point of view of activity, which are the characteristics of this work. In that sense this research was aimed at general: to analyze the activity of professionals working in organizational consultancy in the city of João Pessoa/PB, and as specific objectives: to identif identify the difference from the real-prescribed, the modes of management and labor variability; outline the conditions and organization of work to contextualize the activity of the consultant / analyst RH, to investigate the relationship with the mental work, by identifying the sources of suffering and pleasure, the dynamics of recognition. As theoretical contributions of this study, we used the Work Psychodynamics offering decisive contributions to understanding the issues about subjectivity and mental health at work and Activity Ergonomics, that discipline, to focus on the difference between prescribed work (with the task) and real work (associated with the activity), shows all the effort of managing the variabilities. The work, according to these approaches is not as simple implementation, it always requires a mobilization of workers. As to the method adopted, it was the qualitative approach as the most appropriate, given the need to access the subjective experiences at work. A total of nine consultants from HR (all female) who work in four organizational consultancy in the city of João Pessoa/PB. Data analysis was conducted through Content Analysis, seeking to identify the categories emerging in the speech of the professionals interviewed, in view of the proposed objectives. The results show that the scenario of organizational consultants, charges and pressures, especially from -contracting companies, is one of the biggest factors leading to tension, anxiety and emotional distress for the consultants. The terms "hit process", "you have to go mad," "not for the phone to ring," you must roll, "has much to samba," applicants in depositions, testimony and mental health may be affected by this work. In some consulting division of tasks to be mistaken for an assembly line where each of the consultants is responsible for a stage of the selection process. Wages are an important factor of dissatisfaction, in general, receive a wage mark. However, the satisfaction candidates who obtained the job through consultation, is considered one of the most rewarding forms of recognition. The fact of HR consultants are a bridge, a link between the candidate who is unemployed, and the wave you want it, makes such an intermediated workers important in the process of professional reintegration.